Pengaruh Visual Merchandising, Price Discount, Dan Bonus Pack Terhadap Keputusan Impulse Buying Pada Citra Express Kota Padang - Ardi Abdillah Rahman; Muhammad Abdillah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the influence of merchandising, price discounts, and bonus packs on impulse purchases among customers at Citra Express in Padang City. The increasing interest in spontaneous shopping among consumers, particularly in modern retail, is an important background for this study. Citra Express, as a retailer implementing various promotional strategies such as product layout, price discounts, and bonus offers, is considered interesting to examine in relation to impulse buying behavior. This study was quantitative. Data collection was conducted by distributing questionnaires to 138 respondents using a purposive sampling method. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25 software. The results showed that, partially and simultaneously, the variables merchandising and bonus packs had a positive and significant effect on impulse buying. Price discounts had no significant effect on impulse buying. Thus, the promotional strategies implemented by Citra Express have been proven to encourage consumers to make impulse purchases, especially when products are attractively displayed, discounted, or accompanied by bonus offers.